How Artificial Intelligence is Making Transport Safer, Cleaner, More Reliable and Efficient in Emerging Markets - Lopez Conde, Maria (International Finance Corporation, Washington, DC, 2020)
Transport in emerging markets often faces acute challenges due to poor infrastructure, growing populations, urbanization, and in some regions rising prosperity, which increases vehicle traffic, cargo volumes, and pollution. Artificial intelligence offers new solutions to these challenges by making market entry easier and allowing countries to reach underserved populations, creating markets and private sector investment opportunities associated with them.